2019
DOI: 10.1177/0954406219892301
|View full text |Cite
|
Sign up to set email alerts
|

Vickers hardness indentation size effect in selective laser melted MS1 maraging steel

Abstract: In this paper, selective laser melting fabricated specimens in non-heat-treated and heat-treated conditions were subjected to Vickers microhardness testing, by using a full range of loadings: 10, 25, 50, 100, 200, 300, 500, and 1000 g. Microhardness of longitudinal sections and cross-sections were correlated and the obtained values were plotted against loadings and indentation size effect was studied, in order to find the optimal loading range, that gives the material true microhardness, or load-independent ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
2
3
0
Order By: Relevance
“…The current research reveals that the four theoretical models all exhibit good relevance in regression analyses, as shown in Figure 6 and Table 3 . These results are consistent with the results of other researchers [ 3 , 12 , 26 , 27 , 28 , 29 , 30 , 31 ]. A new finding of current research is that good compatibility of the theoretical models with the measured hardness does not always exist when the indentation load was low, e.g., lower than 0.05 kgf, as shown in Figure 8 .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The current research reveals that the four theoretical models all exhibit good relevance in regression analyses, as shown in Figure 6 and Table 3 . These results are consistent with the results of other researchers [ 3 , 12 , 26 , 27 , 28 , 29 , 30 , 31 ]. A new finding of current research is that good compatibility of the theoretical models with the measured hardness does not always exist when the indentation load was low, e.g., lower than 0.05 kgf, as shown in Figure 8 .…”
Section: Discussionsupporting
confidence: 94%
“…Similar problems also exist in the evaluation of hard coatings, in which microhardness and nano-indentation are still the major methods [ 24 , 25 ]. The established models have enabled microhardness testing to measure the real hardness and hardening behaviour of various materials, such as annealed and strain-hardened stainless steels [ 2 , 26 ], irradiation-hardened vanadium alloys [ 27 ], ceramics and glass [ 28 ], steels of different chemical compositions and hardened conditions [ 12 , 29 , 30 ], and other materials [ 31 , 32 ]. It has been noted however, that few cases were conducted on materials having dimensions down to micro-scales, such as particles, fibers, thin films and micro-scale engineering surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, measurements conducted in the central part of the specimen exhibited a correlation factor of 0.9992, which is higher and thus more adequate than that achieved by the PSR model and equal to the values obtained by applying Meyer's law. These results are similar to those obtained by Gong et al[23], as well as Balos et al[20,25,26], where an added experimental constant P o was found to enhance the accuracy of the model, irrespective of the tested material, i.e., polymers or alloys, obtained as bulk material or additively manufactured, and tested by the Vickers or the Knoop microhardness testing method.…”
supporting
confidence: 90%
“…The behavior showcasing irregular values obtained at different indentation loads, shown in Figure 1 line b, is exhibited by some organic crystals and polymers [24]. The RISE behavior, where an increase in test load influences the increased microhardness values up to a threshold load value, resulting in reaching H LIH , was found in some metals, obtained via selective laser melting (SLM) and tested via Vickers and Knoop microhardness methods [25,26]. Conversely, brittle polymers and ceramics exhibit ISE behavior (Figure 1, line d), where the rise in test load influences the obtaining of lower microhardness values, again up to a threshold load value, which results in reaching H LIH .…”
Section: Of 11mentioning
confidence: 89%
“…Mechanical hardening is described in detail in studies by the authors of [22,23]. Additionally, other researchers have endeavored to identify the influence of material properties on the surface hardening of materials such as Al 6061-T6 [24] and Hadfield steels [25][26][27][28][29][30][31]. The issue of surface hardening in AISI 304 steel is addressed in [32].…”
Section: Introductionmentioning
confidence: 99%